(untitled) (المجلة الدولية للبحوث العلمية, 2025)
The importance of this study is that it is timely and strategically important for both academic research and the growth of institutions in Saudi Arabia. As Saudi universities work to meet the high goals of Vision 2030, encouraging innovation, creativity, and development based on knowledge has become a national priority. Universities are no longer just places to learn and share knowledge. They are today expected to be engines of innovation, coming up with new ideas, solutions, and discoveries that help the country’s social and economic advancement. In this environment, comprehending the influence of organizational culture on fostering innovation among university staff is not only important, but also imperative.